Evaluation of Malathion and Malaoxon Contamination in Buffalo and Cow Milk from Afyonkarahisar Region, Turkey, Using Liquid Chromatography/Tandem Mass Spectrometry – a Short Report - Kara Recep; Ince Sinan (Polish Journal of Food and Nutrition Sciences, 2016)
Organophosphate (OP) pesticides via consumption of milk and milk products induce hazardous effects on human health. Considering their risk to human health, the determination of organophosphate pesticide levels in dairy products is very important. Until now, there has been limited data available on the occurrence of organophosphate pesticides in dairy products in Turkey. The aim of the present study was to investigate the presence of malathion and malaoxon residues in commonly consumed buffalo and cow milk products in the city of Afyonkarahisar, Western Turkey. For this purpose, 75 buffalo and 75 cow milk samples were collected from the city. Malathion and malaoxon levels were determined by means of liquid chromatography/tandem mass spectrometry. In the study, neither malathion nor malaoxan was detected in buffalo and cow milk samples. In conclusion, survey studies were performed continuously for organophosphate pesticide contamination in consumed milk samples and products in Turkey.